Effect of seed pre-treatment with auxin and gibberellin on germination and yield of cowpea (Vigna unguiculata L.) - Fahimeh Darkatanian; Saeed Saeedipour (پژوهش‌های حبوبات ایران)
Introduction Cowpea (Leguminosae: Papilionoidae) represents the main food legume and a versatile crop in tropical region. It is drought tolerant and could perform better growth in warm climates. It is most popular in the semi-arid regions of the tropics where other food legumes are available. This crop has been described as the major source of dietary protein in tropical and subtropical regions of the world especially where animal protein consumptions are low. Efforts made to maximize yield, is largely hampered by adverse effect of abiotic stress such as salinity and drought. These effects cause a huge loss due to low yield and failure of the crop to establish in some cases. Alternative approach towards efficient and cost effective means of production of cowpea in the tropical regions is very desirable. Pre-sowing hardening seed treatment is an easy, low cost and low risk technique and also an alternative approach recently used to overcome the effect of abiotic stresses in agricultural production. Increased germination rate and uniformity have been attributed to metabolic repair during imbibition, buildup of germination enhancing metabolites, osmotic adjustment, and, for seeds that are not redried after treatment, a simple reduction in imbibition lag time. The beneficial effects of priming have also been demonstrated for many field crops such as wheat, sugar beet, maize, soybean and sunflower. The main objective was to assess the physiological effect of Indole 3acetic acid (IAA) and gibberellic acid (GA3) on germination and seedling growth of cowpea.   Material and Methods This experiment was carried out at the Seed Testing Laboratory, Department of Seed Science & Technology, at the Shoushtar University in Iran, with an objective to determine the rate of seed germination and seedling growth which influenced by various concentrations of growth regulators in cowpea (Vigna sinensis L.). Seeds of cowpea were obtained from the International Institute of Agriculture (IITA), Safiabad Research Station., Ahvaz, Iran. Before the start of experiment, seeds were surface sterilized in 1% sodium hypochlorite solution for 3 min, then rinsed with sterilized water and air-dried. Moisture content of seed was determined by using oven at 103 C for 12 hrs and was found 12% as recommended value. Different concentrations of the growth substances prepared in the laboratory were transferred from the reagent bottles into 50mls conical flasks which were clearly labelled according to the concentration of the growth substances to be used in the soaking treatment. The seeds were soaked in the various concentrations of 20, 40 and 60 ppm of GA3 and IAA with a separate control set. These were soaked for 6 or 12 hours in the above concentrations and only double distilled water for the control set. The seeds were sown on moist filter papers in 9cm well labelled petri dishes.   Results and Discussion Emergence rate, root shoot lengths, seedling biomass are all important contributors of seed vigor. Higher emergence rate is the main foundation, which ensures an improvement of overall seedling performance. Seed germination rate varied significantly among the duration and hormone treatment (p < 0.05). The results showed significant increase in the rate of germination for seeds presoaked in the distilled water when compared with various hormones concentrations. Maximum increase of up to about 25 and 71% in compare to presoaked GA3 and IAA was observed. The soaking period of 12 hrs decreased the germination rate and uniformity emergence significantly in respect to 6 hrs treatment. Substantial variation on germination and other aspects were found between treatments. The seeds treated with GA3 showed better performance, in compare with IAA treatments. In comparison, concentrations of GA3 did not show any difference in respect of all measured traits which meant the higher concentration was as good as the lower concentration. Germination rate under the treatments of IAA at all concentrations recorded maximum by 12 hrs soaking. It was observed that for germination enhancement, distilled water was best suited, but in case of plumule length and uniformity emergence, did not show any significant effect with GA3. When the two hormones were compared, gibberellic acid (GA3) was observed more effective and responsive to the regulation of radicle and plumule elongation.   Conclusion The findings of this study revealed that cowpea germination and early seedling growth were promoted by pre-sowing hardening treatments in distilled water. The lower concentration of hormones (20 ppm) was found to be more effective in inducing germination rate, total dry weight and uniformity emergence. Generally, treatment of water priming for 6 hours in the laboratory and in the field was the superior treatment in terms of the predominant criteria measured in bean; therefore, it is presented as the best combination of treatment in this study.